Code-switching amongst UiTM B. Ed. TESL students: awareness, frequency and situations / Adam Zulhilmi Ahmad - Ahmad, Adam Zulhilmi (Faculty of Education, 2014)
Given that code-switching is common in bilingual societies such as Malaysia, Malaysians will often revert to their mother tongue when unable to express themselves instead of finding out the appropriate word to be used in the English language. This linguistic phenomenon has also been observed by the researcher to be prominent amongst B. Ed TESL students. Their reliance on this technique may give detrimental effects to their learning of the language that they will, in future, teach. Thus, this research is aimed to answer the research questions which comprise of whether are UiTM B. Ed TESL students aware of code-switching, how frequent do UiTM B. Ed TESL students code-switch and finally in what situations do UiTM B. Ed TESL students code-switch? The data of this qualitative research design was obtained through semi structured interview which was divided into two; informal and formal. The data that has been obtained from the research yielded results that are rather interesting. The most significant finding is that the B. Ed TESL students code-switch on a regular basis when in an informal linguistic register. It was found that each respondent of the interview code-switched without much hesitation during the informal interview section. Another finding that is of interest is that the respondents, although admittedly unaware of their code-switching tendencies, are able to clearly state with whom they are able to code-switch with and with whom they avoid code-switching.